PERBANDINGAN PENGGUNAAN AGREGAT TIPE SPLIT DAN KORAL TERHADAP KUAT TEKAN BETON FURNISHED - Farlin Rosyad; Aryo Setyaki Syahputra; Wanda Yudha Prawira (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2024)
This research aims to investigate the impact of variations in coarse aggregate mixtures on concrete compressive strength and to compare the effects of using split and coral aggregates on the resulting concrete compressive strength. The experiments were conducted at the laboratory of Bina Darma University, Palembang, South Sumatra, using 54 test specimens in the form of 10 x 20 cm cylinders, divided into 27 test specimens for each split and coral aggregate mixture. The research results indicate that a 10% split aggregate mixture has a significant effect on concrete compressive strength, while a 30% coral aggregate mixture also has a substantial impact on concrete compressive strength, with an inverse relationship to the split aggregate mixture. Furthermore, this study achieved optimal concrete compressive strength test results at 28 days of age, with a 10% split aggregate mixture reaching a compressive strength of 61.34 MPa and a 30% coral aggregate mixture reaching a compressive strength of 47.88 MPa.Keywords: Concrete, Variation of Mixture, Compressive Strenght